2022
DOI: 10.1038/s41467-022-28069-2
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperpolarised 13C-MRI identifies the emergence of a glycolytic cell population within intermediate-risk human prostate cancer

Abstract: Hyperpolarised magnetic resonance imaging (HP 13C-MRI) is an emerging clinical technique to detect [1-13C]lactate production in prostate cancer (PCa) following intravenous injection of hyperpolarised [1-13C]pyruvate. Here we differentiate clinically significant PCa from indolent disease in a low/intermediate-risk population by correlating [1-13C]lactate labelling on MRI with the percentage of Gleason pattern 4 (%GP4) disease. Using immunohistochemistry and spatial transcriptomics, we show that HP 13C-MRI predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(102 citation statements)
references
References 90 publications
7
93
1
1
Order By: Relevance
“…This was a retrospective study of data acquired prospectively as part of an institutional review board–approved (National Research Ethics Service Committee East of England, Cambridge South, 16/EE/0205) study that included patients undergoing radical prostatectomy for biopsy-proven PCa [ 4 ]. All patients underwent 3 T pre-biopsy mpMRI and HP- 13 C-MRI, measuring pyruvate SNR, lactate SNR, TC-SNR, and the pyruvate-to-lactate exchange rate constant ( k PL ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was a retrospective study of data acquired prospectively as part of an institutional review board–approved (National Research Ethics Service Committee East of England, Cambridge South, 16/EE/0205) study that included patients undergoing radical prostatectomy for biopsy-proven PCa [ 4 ]. All patients underwent 3 T pre-biopsy mpMRI and HP- 13 C-MRI, measuring pyruvate SNR, lactate SNR, TC-SNR, and the pyruvate-to-lactate exchange rate constant ( k PL ).…”
Section: Methodsmentioning
confidence: 99%
“…The slides were analysed using HALO v3.2.1851.266 (Indica Labs) and the FISH v2.2.0 module. Epithelial and stromal cell populations were differentiated using a fluorescent random forest tissue classifier [4].…”
Section: Lactate Dehydrogenase Mrna Expression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The first clinical trials of HP-[1- 13 C]-pyruvate MRI and MRSI were successfully used in prostate cancer patients [ 36 ]. Recently, Sushentsev N et al [ 37 ] also found that HP 13C-MRI can noninvasively differentiate indolent from aggressive prostate tumors based on their characteristic metabolic features (Fig. 5 ).…”
Section: Genitourinary System Diseasementioning
confidence: 99%